Intensive cryptic microbial iron cycling in the low iron water column of the meromictic Lake Cadagno. (14th November 2016) - Berg, Jasmine S.; Michellod, Dolma; Pjevac, Petra; Martinez‐Perez, Clara; Buckner, Caroline R. T.; Hach, Philipp F.; Schubert, Carsten J.; Milucka, Jana; Kuypers, Marcel M. M.
Summary: Iron redox reactions play an important role in carbon remineralization, supporting large microbial communities in iron‐rich terrestrial and aquatic sediments. Stratified water columns with comparably low iron concentrations are globally widespread, but microbial iron cycling in these systems has largely been ignored. We found evidence for unexpectedly high iron turnover rates in the low (1–2 µmol·l −1 ) iron waters of Lake Cadagno. Light‐dependent, biological iron oxidation rates (1.4–13.8 µmol·l −1 ·d −1 ) were even higher than in ferruginous lakes with well‐studied microbial iron cycles. This photoferrotrophic iron oxidation may account for up to 10% of total primary production in the chemocline. Iron oxides could not be detected and were presumably reduced immediately by iron‐reducing microorganisms. Sequences of putative iron oxidizers and reducers were retrieved from in situ 16S rRNA gene amplicon libraries and some of these bacteria were identified in our enrichment cultures supplemented with Fe(II) and FeS. Based on our results, we propose a model in which iron is oxidized by photoferrotrophs and microaerophiles, and iron oxides are immediately reduced by heterotrophic iron reducers, resulting in a cryptic iron cycle. We hypothesize that microbial iron cycling may be more prevalent in water column redoxclines, especially those within the photic zone, than previously believed.